2019
DOI: 10.1055/a-0953-6007
|View full text |Cite
|
Sign up to set email alerts
|

Halimium halimifolium: From the Chemical and Functional Characterization to a Nutraceutical Ingredient Design

Abstract: Halimium halimifolium (Hh) is a shrub used in Algerian folk medicine to treat gastrointestinal pain. An UHPLC-PDA-ESI/MSn method was developed to identify the metabolic profile of the traditionally used infusion (Hh-A) from the aerial parts. The structures of flavanols were confirmed by NMR analysis after the isolation procedure from a hydrohalcolic extract (Hh-B) that also allowed for the identification of phenolic acids, an aryl butanol glucoside, and different derivatives of quercetin, myricetin, and kaempf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
2
7
0
Order By: Relevance
“…All of the four antihyperglycaemic studies were enzyme‐based assays investigating the inhibition of α‐amylase or α‐glucosidase, two of the major enzymes responsible for cleaving simple sugars from starch and glycogen. Two of the studies reported moderate antihyperglycaemic activity (Sut et al, 2020; Tasnuva et al, 2019), while the other two studies found relatively high activity compared to the positive control used (Kerbab et al, 2019; Quispe et al, 2017). Inhibition activity against α‐amylase and α‐glucosidase is not necessarily correlated, with Kerbab et al (2019) reporting trans ‐tiliroside as a potent inhibitor of α‐amylase, but not of α‐glucosidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the four antihyperglycaemic studies were enzyme‐based assays investigating the inhibition of α‐amylase or α‐glucosidase, two of the major enzymes responsible for cleaving simple sugars from starch and glycogen. Two of the studies reported moderate antihyperglycaemic activity (Sut et al, 2020; Tasnuva et al, 2019), while the other two studies found relatively high activity compared to the positive control used (Kerbab et al, 2019; Quispe et al, 2017). Inhibition activity against α‐amylase and α‐glucosidase is not necessarily correlated, with Kerbab et al (2019) reporting trans ‐tiliroside as a potent inhibitor of α‐amylase, but not of α‐glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the studies reported moderate antihyperglycaemic activity (Sut et al, 2020;Tasnuva et al, 2019), while the other two studies found relatively high activity compared to the positive control used (Kerbab et al, 2019;Quispe et al, 2017). Inhibition activity against α-amylase and α-glucosidase is not necessarily correlated, with Kerbab et al (2019) reporting trans-tiliroside as a potent inhibitor of α-amylase, but not of α-glucosidase. Similarly, Quispe et al (2017) found kaempferol 3-O-glucuronide to strongly inhibit aldose reductase but not α-glucosidase.…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…A375, HeLa, and A549 were plated on multiwell plates, and serial dilutions of AJ (200−100−50 µg/mL), compounds (75−50−25 µg/mL), AJEP 3 microparticles (0.5−1.0−1.5 mg/mL) were added for one hour, and then co-exposed to lipopolysaccharide (LPS), from Escherichia coli , (0.1 µg/mL) for 24 h in order to evaluate the antioxidant activity of extract (AJ), isolated compounds ( 1 – 6 ), and AJEP 3 microparticles [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant activity of AJ, compounds, and AJEP 3 microparticles was investigated using a cytofluorimetric assay, 2′–7′-dichlorofluorescein diacetate (H 2 DCF-DA), usually adopted to evaluate the intracellular production of peroxides [ 32 ]. H 2 DCF-DA is a non-polar molecule that easily diffuses inside cells and it is hydrolysed by intracellular esterases that remove the acetate groups making it polar and therefore impermeable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation